2009
DOI: 10.1007/s00464-009-0348-z
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the short-term clinicopathologic outcomes of laparoscopic surgery versus conventional open surgery for transverse colon cancer

Abstract: Laparoscopic and conventional open surgeries were found to have similar clinical outcomes in transverse colon cancer, and the oncologic quality of laparoscopic surgery was found to be acceptable compared with conventional open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 17 publications
1
43
2
Order By: Relevance
“…Our results contrasted with those reported by some laparoscopic experts. [20][21][22] Laparoscopically assisted resection of transverse colon cancer was reported to take significantly longer in terms of operative time than laparoscopically assisted resection of cancer at other sites 20,21 or conventional open surgery 22 for transverse colon cancer; although reports 23,24 from Korea show that no significant difference was found in such comparisons. In addition, 2 study groups 20,21 suggested that laparoscopically assisted resection of transverse colon cancer may have an insignificant higher rate of postoperative complications, which should not be ignored and may be a reflection of the greater complexity associated with the resection of transverse colon, compared with other less challenging segmental colectomies.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Our results contrasted with those reported by some laparoscopic experts. [20][21][22] Laparoscopically assisted resection of transverse colon cancer was reported to take significantly longer in terms of operative time than laparoscopically assisted resection of cancer at other sites 20,21 or conventional open surgery 22 for transverse colon cancer; although reports 23,24 from Korea show that no significant difference was found in such comparisons. In addition, 2 study groups 20,21 suggested that laparoscopically assisted resection of transverse colon cancer may have an insignificant higher rate of postoperative complications, which should not be ignored and may be a reflection of the greater complexity associated with the resection of transverse colon, compared with other less challenging segmental colectomies.…”
Section: Discussionmentioning
confidence: 49%
“…In addition, 2 study groups 20,21 suggested that laparoscopically assisted resection of transverse colon cancer may have an insignificant higher rate of postoperative complications, which should not be ignored and may be a reflection of the greater complexity associated with the resection of transverse colon, compared with other less challenging segmental colectomies. When our minilaparotomy series is compared with recently reported series of laparoscopically assisted resection in terms of operative time, blood loss, and postoperative complications, the mean operative time (133.5 minutes) is markedly shorter in our minilaparotomy series than those (203.6-260 minutes) [20][21][22][23][24] of reported laparoscopically assisted series, and the blood loss and the incidence of postoperative complications seem to be compatible to or smaller than those of laparoscopically assisted series. On the basis of our results, we feel that lymph node dissection around the middle colic vessels via the minilaparotomy approach is not difficult compared with conventional open surgery, although there is a knack to exposing the superior mesenteric vessels via minilaparotomy, as described in our surgical procedures.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Most agreed towards significantly less blood loss with laparoscopy [5,6,10]. One criticism for some initial studies was the high conversion rates, e.g., 21 % in the COST study.…”
Section: Discussionmentioning
confidence: 99%
“…There have been three reports of laparoscopic -assisted transverse cancer resection, supporting its feasibility, since 2007 26,27) . Kim et al 27) published a comparative study on the short -term clinico -pathologic outcomes of LAC (n = 37) vs. OC (n = 50) for transverse colon lesions.…”
Section: Transverse Colon Cancermentioning
confidence: 99%